Trump pressuring the Fed - Peter Tillmann (Philipps-University Marburg, School of Business and Economics, 2019)
After appointing Federal Reserve Chairman Powell, President Trump steadily put pressure on the Fed to cut interest rates. We show that, on average, a statement from Trump led to lower long-term interest rates, consistent with expectations of lower expected future short rates. However, the impact of Trump's statements declined over time.
Keywords: 330; Federal Reserve; monetary policy; yield curve; political economy; central bank independence